Evaluation of C-Band SAR for Identification of Flooded Vegetation in Emergency Response Products. Issue 1 (2nd January 2019) - Brisco, Brian; Shelat, Yask; Murnaghan, Kevin; Montgomery, Joshua; Fuss, Colleen; Olthof, Ian; Hopkinson, Chris; Deschamps, Alice; Poncos, Valentin
Abstract: A synthetic aperture radar (SAR) data set of the Peace Athabasca Delta, Alberta, was used to evaluate approaches to flooded vegetation mapping. A primary objective was to identify how to add a flooded vegetation layer to the Emergency Geomatics Service (EGS) SAR-derived flood products. Field data were used to identify non-flooded and flooded vegetation. A combination of statistical analyses and box plot visual inspection was used to evaluate the magnitude-only images, the polarimetric and compact polarimetric parameters/decompositions, and the coherence products for mapping flooded vegetation. This paper provides some background on the use of SAR for flood mapping, describes the data and processing methods, and presents the results of this comparison. To some degree all polarizations and techniques were effective for mapping flooded vegetation due to the increased backscatter intensity and the phase shift from the double bounce scattering. In particular, all polarization combinations, the HH/HV ratio, Shannon entropy, and the m-chi double bounce produce good separation. The water/vegetation interface remains coherent when flooded, also allowing flooded vegetation to be identified with seasonal coherence. These results demonstrate that the use of multi-mode RADARSAT Constellation Mission data for providing a flooded vegetation layer to EGS flood maps is possible.